Comparison of Different Hollow Cone Water Sprays For Continuous Miner Dust Control Applications - S. Klima; C. Seaman; S. Mischler; J. Organiscak (Society for Mining, Metallurgy & Exploration, 2017)
"Researchers at the National Institute for Occupational Safety and Health’s Pittsburgh Mining Research Division (PMRD) performed comparative testing of six hollow cone water sprays from three manufacturers: static swirl chamber sprays from Spraying Systems (BD-3, BD-5) and Steinen-Hahn (SH-3, SH-5), and movable swirl chamber sprays from Repair King (RK-3, RK-5). Water flow testing was completed at three operating pressures (60, 80, and 100 psig) where both sets of sprays (3-series and 5-series) produced similar water flows, deviating less than 8% from the average water flow rate at each pressure. Airflow induction testing was completed at 80 psig using a hot wire anemometer to take air velocity measurements upstream of the spray nozzles. Respirable dust capture efficiency testing was completed in a 14.5-m3 (512-ft3) closed system dust chamber at 80 psig. The dust capture efficiency ranged from 7.2% to 9.9% for the 3-series nozzles, and from 5.3% to 7.1% for the 5-series nozzles. Sprays were also analyzed using a Cloud Aerosol and Precipitation Spectrometer (CAPS), which uses light scattering to count and size the airborne water droplets from each spray. In both cases, Spraying Systems sprays produced the largest mean droplet size, followed by Steinen-Hahn and Repair King sprays, respectively. INTRODUCTION Coal mine worker overexposure to respirable coal dust continues to be a problem in underground coal mining operations in the United States. The U.S. Mine Safety and Health Administration (MSHA) now requires coal mine worker respirable dust exposure to be no more than 1.5 mg/m3 average over the actual working shift (CFR 30-70.100, 2016). Potential overexposure to respirable dust by continuous miner, roof bolter, and shuttle car operators may be prevented if proper safety and health practices are implemented as detailed in the mine’s ventilation plan (CFR 30-75.371, 2016). Water sprays are a necessary component of an underground coal mine ventilation plan. They are important on the continuous mining unit for moving air and removing respirable coal dust from the breathable airstream. MSHA requires underground coal mines to include the number, types, location, orientation, operating pressure, and flow rate of operating water sprays in their mine ventilation plans (CFR 30-75.371, 2016). Water sprays can become clogged, requiring the sprays to be properly checked, maintained, and replaced in order to continue meeting the ventilation requirements described in the mine ventilation plan.In an effort to eliminate the problems with spray clogging, Repair King has developed self-cleaning movable swirl chamber hollow cone water sprays (RK-3, RK-5). The spray’s movable swirl chamber is designed to only open when water pressure is applied to the spray nozzle, preventing the nozzle from clogging. Anti-clogging sprays could improve mine production by reducing the amount of time spent servicing clogged sprays. Also, these sprays could improve health and safety of miners since they would continue to suppress and capture dust and continue to move airflow at the face, while a clogged spray loses this ability until it is cleaned or replaced manually. The objective of this research was to assess the comparability of the Repair King sprays with the most commonly used sprays in underground coal mines using performance criteria. An assessment of the sprays self-cleaning or anti-clogging capability was not conducted."